2006
DOI: 10.1152/ajpcell.00134.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic potassium controls CFTR deactivation in human sweat duct

Abstract: Reddy, M. M., and P. M. Quinton. Cytosolic potassium controls CFTR deactivation in human sweat duct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 36 publications
0
16
0
1
Order By: Relevance
“…other native tissues, the sweat gland reinforces the lesson that CFTR functions in a pivotal role to couple transport activity with transport capacity and cell energy supply on a moment-to-moment basis (113,123,124,133,137).…”
Section: Cftr and Phosphatases Lesson 12: Cftr Clconductance Is Deacmentioning
confidence: 63%
“…other native tissues, the sweat gland reinforces the lesson that CFTR functions in a pivotal role to couple transport activity with transport capacity and cell energy supply on a moment-to-moment basis (113,123,124,133,137).…”
Section: Cftr and Phosphatases Lesson 12: Cftr Clconductance Is Deacmentioning
confidence: 63%
“…3, and ). After wash‐out of high [K + ], the V m returned to baseline with an undershoot that was consistent with the activation of the Na + –K + pump when the extracellular [K + ] is elevated (Reddy & Quinton, 1991, 2006).…”
mentioning
confidence: 55%
“…As a general example of this type of regulation, it has recently been shown that declining intracellular potassium deactivates via dephosphorylation the cystic fibrosis transmembrane conductance regulator (CFTR) Cl -channel limiting the apical influx of Cl -and Na + until the intracellular concentration of potassium is stabilized [67]. In regards to AVD and apoptosis, cultured cortical neurons treated with staurosporine or ceramide resulted in an inhibition of chloride currents preventing apoptotic cell shrinkage.…”
Section: Potassium As a Signal For Apoptosismentioning
confidence: 99%